Análisis de contenidos de la FanPage de Facebook y la página oficial del GAD Provincial de Bolívar y su influencia en la opinión pública del cantón Guaranda, año 2023 - Arevalo Calderon, Mayra Karolina (2024)
This research is a description of the information management of a public institution through a digital platform whose main objective was to analyze the contents of the Facebook FanPage and the official page of the Autonomous Decentralized Provincial Government of Bolivar and its influence on public opinion in the citizens of the canton of Guaranda. From the perspective of social constructivism I can understand the management of information within the masses generates a construct of critical and reflective thinking to what is called public opinion, for this reason it is important that government institutions such as the GADPB object of this study is concerned about the management of the information issued by the official page and the Facebook FanPage in order to generate positive thinking in public opinion and at the same time contribute to the positioning of its image. Statistical tools were used; quantitative and qualitative, as well as interviews, surveys to citizens and members of the Institutional Communication Management Department. Through their understanding, crisis communication strategies were developed and expressed through a Crisis Management Manual to promote a favorable perception of the GADPB and strengthen its reputation in the digital environment and social networks.